O efeito da adubação verde em sistemas agroflorestais na melhoria da qualidade do solo no município de Pacajá-Pará - LISBOA, Sâmia Cristina de Lima (2021)
In the Amazon, Agroforestry Systems (SAFs) are one of the best alternatives for sustainable agriculture when compared to the traditional system, and they are perfectly suited to the restoration of forests, and represent a more committed way to current environmental issues. The cultivation of agroforestry in small areas favors the intercropping of short-cycle plants, which are more immediately consumed while providing the regeneration of the area by the permanence of the tree content. Under these conditions, it is necessary to understand the mechanisms of conservation of nutrients in forests that allow their exploitation, as well as the implementation of sustainable crop production systems, especially those of agroforestry systems that form a structure similar to those of natural vegetation. The objective of this work was to evaluate the dynamics of soil physical and chemical attributes in two sampling periods (rainy and dry) in agroforestry systems (SAFs) compared to soil in secondary vegetation conditions in the municipality of Pacajá Pará. implemented in 2016 in partnership with the Federal University of Pará - Campus Altamira and Roberto Marinho Foundation for the Forestry program that used the area to deploy a demonstration unit for the region. The experiment of this research were performed in completely randomized blocks (DIC), with three treatments, and these treatments were divided into two repetitions named in R1 and R2. The areas where the SAFs were implanted are of secondary vegetation origin which were submitted to the grating process and part of this system introduced guandu bean planting. Thus, the following treatments are constituted in this research: T1 Veg.Secondary or control, T2 or SAF C/G area there was introduction of Guandu with nomenclature and T3 or SAF S/ G which also corresponds to SAF area but only with unused grating of green manure. Soil chemical attributes differed between treatments regardless of period. In general, T2 presented better results regarding the chemical attributes in the rainy and dry season and better soil decompression when evaluating the DS from one period to the other, although it did not present lower density, but the reduction occurred more rapidly when compared to other treatments. The analyzed treatments presented better fertility in the dry period compared to the rainy season, being the areas of SAFs superior in the fertility level compared to the secondary vegetation. The result of better fertility for SAFs areas can be explained by the system implantation besides important role that guandu bean promoted to the soil, significantly influencing the fertility of the site, due to the nutrients and organic matter input left by the legume thinning. , leading to better performance both in the density evaluation and in the values of the chemical attributes analyzed.